Single-dose gadobutrol in comparison with single-dose gadobenate dimeglumine for magnetic resonance imaging of chronic myocardial infarction at 3 T - Wildgruber, Moritz; Stadlbauer, Thomas; Rasper, Michael; Hapfelmeier, Alexander; Zelger, Otto; Eckstein, Hans Henning; Halle, Martin; Rummeny, Ernst J.; Huber, Armin M. (Investigative Radiology, 2014)
Objectives: The aim of this study was to compare the contrast-to-noise ratio (CNR) values of infarct and remote myocardium as well as infarct and blood after application of 0.1 mmol/kg gadobutrol and 0.1 mmol/kg gadobenate dimeglumine on late gadolinium enhancement magnetic resonance (MR) images. Material and Methods: The study was a prospective randomized controlled clinical study. After informed consent was obtained, 20 patients (12 men, 8 women; mean age, 67 ±11 years) with known chronic myocardial infarction were included for an intraindividual comparison of a single-dose gadobutrol and a single-dose gadobenate dimeglumine. Two MR imaging examinations were performed within a period of 28 days in a crossover design. Late gadolinium enhancement imaging was performed 10 minutes after gadolinium administration using a 2-dimensional phase-sensitive inversion recovery gradient echo sequence at 3 T. Infarct size, signal intensities (SIs), signal-to-noise ratio, and CNR were determined on phase-sensitive MR images. Values for CNRWere Calculated as CNRinfarct/myocardium - (Slinfarct-Slmyocardium)/SDnoise and CNRinfarct/blood = (SIinfarct - SIblood)/SDnoise. In addition, the areas of myocardial infarction were determined on single slices. The entire infarct volumes were calculated by adding the areas with hyperenhancement multiplied by the slice thickness. Results: Late gadolinium enhancement was present in all patients. Median values of the infarct area, infarct volume, and transmurality for gadobutrol and gadobenate dimeglumine showed good to excellent concordance (rc = 0.85, rc = 0.95, and rc = 0.71, respectively). The mean signal-to-noise ratio values for infarct, remote myocardium, and ventricular blood were 18.6 ± 6.5,4.1 ± 3.7, and 14.6 ± 7.5, respectively, for gadobutrol and 18.8 ± 8.9,4.9 + 4.5, and 17.8 ± 10.1, respectively, for gadobenate dimeglumine (P = 0.93, P = 0.48, and P = 0.149, respectively). The mean values of CNRinfarct/myocardiumand CNRinfarct/blood were 14.5 ± 5.9 and 4.0 ± 4.6, respectively, for gadobutrol and 13.9 + 6.1 and 0.9 + 4.5, respectively, for gadobenate dimeglumine (P = 0.69 and P = 0.02, respectively). Conclusion: Both gadobutrol and gadobenate dimeglumine allow for successful late gadolinium enhancement imaging of chronic myocardial infarction after a single-dose application (0.1 mmol/kg) at 3 T. Gadobutrol provides a higher CNR between infarct and blood. The CNRs between infarct and normal myocardium, infarct size, and transmural extent were similar for both contrast agents.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast agent; Late gadolinium enhancement; Magnetic resonance imaging; Myocardial infarction